Oestrogen receptor negative breast cancers exhibit high cytokine content - Chavey, Carine; Bibeau, Frédéric; Gourgou-Bourgade, Sophie; Burlinchon, Sandrine; Boissière, Florence; Laune, Daniel; Roques, Sylvie; Lazennec, Gwendal (Breast cancer research : BCR, 2007)
An emerging hypothesis suggests that cytokines could play an important role in cancer as potential modulators of angiogenesis and leucocyte infiltration. A novel multiplexed flow cytometry technology was used to measure the expression of 17 cytokines (IL-1beta, IL-2, IL-4, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12 [p70], IL-13, IL-17, granulocyte colony-stimulating factor [CSF], granulocyte-macrophage CSF, IFN-gamma, monocyte chemoattractant protein [MCP]-1, macrophage inflammatory protein [MIP]-1beta, tumour necrosis factor [TNF]-alpha) at the protein level in 105 breast carcinoma. B lymphocyte, T lymphocyte and macrophage levels were determined by immunohistochemistry. Fourteen of the 17 cytokines were expressed in breast carcinoma, whereas only nine cytokines could be detected in normal breast. Most cytokines were more abundant in breast carcinoma than in normal breast, with IL-6, IL-8, granulocyte CSF, IFN-gamma, MCP-1 and MIP-1beta being very abundant. IL-2, IL-6, IL-8, IL-10, IFN-gamma, MCP-1, MIP-1beta and TNF-alpha, and to a lesser extent IL-1beta and IL-13 exhibited levels of expression that were inversely correlated to oestrogen receptor and progesterone receptor status. Most cytokines were not correlated with age at cancer diagnosis, tumour size, histological type, or lymph node status. However, IL-1beta, IL-6, IL-8, IL-10, IL-12, MCP-1 and MIP-1beta were more abundant in high-grade tumours than in low-grade tumours. In addition, IL-8 and MIP-1beta were expressed to a greater degree in HER2-positive than in HER2-negative patients. The expression of most of the studied cytokines was correlated to levels of activator protein-1, which is known to regulate numerous cytokines. Overexpression of MCP-1 and MIP-1beta were linked to B lymphocyte, T lymphocyte and macrophage infiltration, whereas high levels of IL-8 were correlated with high macrophage content in tumour. Moreover, IL-8 positive tumours exhibited increased vascularization. We found that multiple cytokines were overexpressed in oestrogen receptor negative breast carcinoma, and that the three major cytokines--MCP-1, MIP-1beta and IL-8--were correlated with inflammatory cell component, which could account for the aggressiveness of these tumours.